Abdominal splenosis with acute torsion of an omental splenule - Kelly A. Carman; Bryan S. Walters; Alfred P. Kennedy (Elsevier, 2018)
Abdominal splenosis can be an unexpected source of abdominal pain. Clinically, this diagnosis may be easily confused for any number of infectious or functional etiologies. Additionally, implanted splenules can evade radiographic testing. We report a case of torsed splenic implant masquerading as a delayed presentation of blunt abdominal trauma. The presence of splenosis should be included as a potential source for abdominal pain in patients who are post-splenectomy. Keywords: Splenosis, Splenectomy, Torsion